GENOTYPING AND ANALYSIS OF rs911271 POLYMORPHISM FOR INTRACRANIAL ANEURYSM - Erdemir, Aysegul; Ozkan, Ebru; Gusner, Nurten Turan; Selcuk, Hakan H.; Kara, Batuhan; Baskin, Yasemin; Ellidokuz, Hulya; Balik, Hasan H.; Balik, Dilek Turgut (YILDIZ TECHNICAL UNIV, 2015)
Intracranial aneurysms (IA) are balloon like dilation of the intracranial arterial wall in the brain. It affects %2-5 of the general population and arise from the action of multiple genetic and environmental risk factors. Single nucleotide polymorphisms (SNPs) are variations at a single position in a DNA sequence among individuals and they are associated with certain diseases to evaluate an individual's genetic predisposition to develop a disease. Recently, several SNPs associated with IA have been identified in genome-wide association studies. To our knowledge, the effects of these SNP's in Turkish population has not been studied and this arises great necessity to study them. In this study it is aimed to genotype and analyze rs911271 polymorphism, known to be associated with IA in different populations, to determine genetic risk predisposition of this SNP in Turkish population. Genotyping of rs911271 polymorphism was conducted by using the iPLEX assay in study group which consists of 105 intracranial aneurysm patients and 102 healty controls. Findings of this study showed that there is a lack of association between rs911271 and intracranial aneurysm in Turkish population. Despite the odds ratio was determined as 1,03 (95% CI=0,70-1,51) for carriers of any A allele, this result was not associated with IA in our population because of having a p value of 0,890.
Keywords: Intracranial aneurysm; single nucleotide polymorphism (SNP); SNP genotyping.; Engineering